Pilot Program in Surgical Anatomy Education for Complex Cranial and Skull Base Procedures: Curriculum Overview and Initial 2-Year Experience at Mayo Clinic - Capp, Juliana C.; Bauman, Megan M.J.; Graffeo, Christopher S.; Carlstrom, Lucas P.; Perry, Avital; Pinheiro-Neto, Carlos D.; Gompel, Jamie J. Van; Daniels, David J.; Link, Michael J.; Leonel, Luciano C.P.C.; Peris-Celda, Maria (Journal of Neurological Surgery Part B: Skull Base, 2024)
Background Cadaveric dissection remains a preferred and irreplaceable learning modality among neurosurgery residents. We aimed to develop and describe a tiered, quantifiable, and practical curriculum for cranial neurosurgical anatomy education. We report the structure and evaluation of our 2-year pilot study to serve as a suggested guide for other neurosurgery programs.Methods Our Complex Cranial Dissection Program is tailored to the needs of junior-level neurosurgery residents based on their postgraduation years 1 to 4. Dissections are performed in a sequential manner, each of which emphasize a particular set of manual skills and neuroanatomical knowledge. Dissections are scored on a scale of 10 points. The grading was based on specific landmarks and anatomical structures, which need to be exposed, explored, and preserved.Results Out of 16 residents, 14 individuals (87.5%) attended the dissections in the first iteration of the program and 16 individuals (100%) attended the dissections in the second iteration. A total of 17 dissections were performed across all years. In survey feedback about the program, 100% (Year 1) and 94% (Year 2) of residents considered the assigned dissections to be appropriate for their respective training levels. Further, 100% (Year 1) and 94% (Year 2) of residents endorsed that the dissections were important and helpful for their practice prior to similar operating room experiences.Conclusion The development and implementation of structured dissection programs within residency training, along with dedicated staff, and objective feedback serve a crucial role in neurosurgical education to further develop and enhance surgical skills in the operative setting.
Keywords: neurosurgical education; neuroanatomy; skull base anatomy; neurosurgery resident education